Analisis Viskositas Oli Melalui Pengujian Eksperimental dengan Prototipe Berbasis Stokes' Law - Janitra, Atikah Ayu; Setiyawan, Trio (Universitas Garut, 2025)
This study aims to analyze research data in the form of dynamic-kinematic viscosity values ​​of two types of oil, namely SAE 30 and SAE 50, using the falling ball method based on Stokes' Law through an experimental prototype. Data were collected by measuring the falling time of a sphere through a fluid column and subsequently analyzed statistically. The measurement results showed that SAE 50 consistently resulted higher viscosity values (ranging from 288 to 365 kg/m·s) compared to SAE 30 (ranging from 174 to 252 kg/m·s), aligning with their respective viscosity characteristics. The Anderson-Darling normality test yielded AD values of 0.266 for SAE 30 and 0.319 for SAE 50, with p-values above 0.05, indicating that the data follow a normal distribution. These findings support the effectiveness of the falling ball method as a simple, economical, and accurate approach for characterizing fluid viscosity, both in experimental applications and educational settings in fluid mechanics.